BIBLIOGRAPHICAL SOURCES ON MUSIC THERAPY IN NIGERIA. - Aluede, Charles Onomudo (Voices: A World Forum for Music Therapy, 2009)
Issues relating to health and healing are quite often very primary in the minds of every Nigerian. This is why in the country, short phrases, sentences and proverbs in appreciation of good health are either constantly said or inscribed on door lintels and vehicles by their owners. The eminence of health is captured in texts such as: Health is Wealth, When Health is Lost all is Lost, No Sickness No Suffering, Death is a small enemy but Sickness is The Great Destroyer. These comments are indicative of the peoples’ views of illness and its effect on the society. To combat illness, allopathic and other forms of therapies are used. Music without doubt, remains one of such. In this regard, music is employed in diverse ways to obtain healthful and healing consequence by the people. Arising from the above, this paper identifies the works so far done in the area of Music therapy in Nigeria. It is the hope of this researcher that this step will help contemporary scholars and enthusiasts venturing into this field to find resource materials to rely on as they conduct field research and experiments.